The Influence of Trust, Product Diversity and Product Quality on Purchasing Decisions at PT Kinta Sukses Cemerlang - Winata, Hendly; Hikmah (STIE Tri Bhakti, 2025)
The advancement of digital technology has revolutionized the way companies interact with their consumers, including in influencing the purchasing decision-making process. This study aims to examine the extent to which consumer trust, product variety offered, and product quality play a role in shaping purchasing decisions at PT Kinta Sukses Cemerlang. Using a quantitative approach with a descriptive design, this study involved 327 customers as the population, with 180 respondents selected through the Slovin formula and simple random sampling techniques. The analysis process includes validity and reliability tests, classical assumption checks, multiple linear regression, and hypothesis testing through t-tests and F-tests. The results of the study indicate that partially, trust, product variety, and product quality have a positive and significant influence on purchasing decisions. This finding is also reinforced simultaneously, where the three variables together show a real contribution to increasing customer decisions in purchasing. Overall, these results confirm that the company's strategy in building trust, offering a variety of product choices, and maintaining product quality consistently are key steps in optimizing consumer purchasing decisions.